Heat transfer modeling and temperature experiments of crystalline silicon photovoltaic modules. (April 2017) - Du, Ying; Tao, Wusong; Liu, Yafeng; Jiang, Jianhui; Huang, Haisheng
Highlights: The time-dependent heat transfer model was created using COMSOL Multiphysics. The thermal behavior of the implemented module during operation was simulated. The thermal performance of three photovoltaic modules was measured. The temperature uniform and heat dispersion of modules were compared. Abstract: In this study, the time-dependent thermal performance of crystalline silicon photovoltaic (PV) modules with glass-glass (GG) and glass-back sheet (GB) configurations were investigated. A heat transfer model for PV modules was created in COMSOL Multiphysics environment, to illustrate the time dependent thermal behavior of the implemented module during operation. A thorough understanding of the heat sources, temperature distribution, as well as the performance of heat dispersion and temperature uniform by the solar module in operation was presented with colorful maps, graphs and temperature difference between different locations within PV module. All the analysis leading to the conclusions that the GG modules has a better temperature uniform and heat dispersion performance with respect to GB module although GG module undertakes a slightly higher temperature. However, the temperature of GG module can also be reduced by choosing proper encapsulate and protective covers.